Ata Sodha dalam Tarian Gawi Desa Tenda Kecamatan Wolojita Kabupaten Ende NTT - Hiasynta Merdeka Ayu Heppi (Department of Anthropology Udayana University, 2020)
Gawi dance’s one of the dance that has recorded as an Warisan Budaya Tak Benda (WBTB) but has not been designated as a national cultural. Literally, the meaning of the word GAWI is defined as follows: GA means reluctant or shy while WI means interesting, in the sense of uniting oneself.Ata Sodha is a poet using language of customs. Ata Sodha possess a role as a leader of Gawi dance and it belongs to a part of traditional ceremony. The probleems of this stuudy comprise of (1) How is the role of Ata Sodhain traditional ceremony Gawi dance of Tenda village community? (2) How is the perception of community regarding to Ata Sodha?. The theories being used in this research, namely role theory and simbolic interpretative theory.The concepts that are used among other: roles, Ata Sodha, Gawi dance and perception. In this reserch, descriptive qualitative method’s adopted, by the data source namely primary and secondary in which the data are collected by observing, interviewing literature review.The findings In this research points out that an Ata Sodha has an unseparable role in traditional ceremony. The brainwave that they obtain from their ancestors in form of ability to chant prayer and praise verses by using traditional language to make Ata Sodha have sufficient important role. In traditional ceremony, Ata Sodha plays the role as the lader in Gawi dance. Society expects that the existence of Ata Sodha remains exist in traditional ceremony